EXPERIMENTAL INVESTIGATION OF SCOUR DOWNSTREAM OF A C-TYPE TRAPEZOIDAL PIANO KEY WEIR WITH STILLING BASIN - Qasim Rdhaiwi, Ali; Khoshfetrat, Ali; Fathi, Amirhossein (Journal of Engineering and Sustainable Development, 2023)
In recent years, engineers have focused on finding a solution to reduce scouring downstream of piano key weirs. Piano key weirs have high efficiency in flood flow and a higher discharge coefficient. In this research, a type C trapezoidal piano key weir with a type 1 stilling basin was used. Three discharges and three water depths were also used. The results showed that the existence of the stilling basin reduces scour. In the weir with the stilling basin, the maximum scour depth is reduced and the scouring hole becomes more elongated. The maximum distance of the scouring depth increases compared to the toe of the weir. The maximum scour depth and the maximum scour depth distance in the weirs with the stilling basin are about 63.4% less and 20.4% more, respectively than in the weirs without the stilling basin. Additionally, by increasing the flow rate and decreasing the depth of the downstream flow, the amount of scour increases.